Dielectric properties of peanut kernels associated with microwave and radio frequency drying. (May 2016) - Zhang, Shuang; Zhou, Liyang; Ling, Bo; Wang, Shaojin
Abstract : To develop advanced drying methods based on microwave (MW) and radio frequency (RF) heating, knowledge of dielectric properties is essential for understanding the interaction between electromagnetic fields and peanuts. In this study, dielectric properties of peanut kernels were measured between 10 and 4500 MHz using an open-ended coaxial-line probe and network analyser at temperatures between 25 and 85 °C and moisture contents between 10% and 30% on a wet basis (w.b.). The results showed that both dielectric constant and loss factor of peanut kernels decreased sharply with increasing frequency over RF range (10–300 MHz), but gradually over the MW range (300–4500 MHz). Both dielectric constant and loss factor increased with increasing moisture content and temperature. The rate of increase was greater at higher temperature and moisture levels than at their lower levels. Penetration depth decreased with increasing frequency, moisture constant, and temperature. The measured dielectric properties were finally applied to determine the temperature profiles of RF heated samples under three moisture levels using experiment and simulation. This study on dielectric properties may provide useful guidelines in developing effective dielectric drying methods with a suitable drying thickness for peanuts. Highlights: Dielectric properties of peanut kernels were studied by network analyzer. Dielectric properties increased with decreasing frequency, and increasing moisture and temperature. Penetration depth decreased with increasing frequency, moisture, and temperature. Phenomenon of "moisture leveling" and "thermal run away" effects was discussed.